"La Casa de la Troya". A Vision of Galicia on Paper and in Nitrate - Vaquero Argelés, María (Madrygal. Revista de Estudios Gallegos, 2015)
This article aims to make a comparative study between the novel and the film. What we find interesting in this analysis is that both works were created by the same author: Alejandro Pérez Lugin. We also try to obtain information that will allow us to classify the film as a Galician production.